2023
DOI: 10.3390/buildings14010098
|View full text |Cite
|
Sign up to set email alerts
|

The Interactive Effects of Communication Network Structure and Organizational Size on Task Performance in Project-Based Organizations: The Mediating Role of Bootleg Innovation Behavior

Xue Ding,
Long Feng,
Yao Huang
et al.

Abstract: A PBO is a temporary organization formed by assembling members with diverse experiences and backgrounds, aimed at achieving specific innovation goals. Constructing a reasonable communication network structure and enhancing organizational synergy are effective ways to promote the sustainable development of the system. This study, based on the Input–Process–Output (IPO) model and social network analysis, utilized a group collaboration platform to conduct a three-stage communication experiment on 685 construction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 100 publications
(113 reference statements)
0
1
0
Order By: Relevance
“…Drawing upon the existing research on communication networks of engineering project teams featured in mainstream peer-reviewed papers and case studies [32][33][34], this study summarizes four types of communication networks. These networks include the fully connected network, the subgroup network, the core-periphery network, and the locally clustered network.…”
Section: Pbos and Communication Network Structurementioning
confidence: 99%
“…Drawing upon the existing research on communication networks of engineering project teams featured in mainstream peer-reviewed papers and case studies [32][33][34], this study summarizes four types of communication networks. These networks include the fully connected network, the subgroup network, the core-periphery network, and the locally clustered network.…”
Section: Pbos and Communication Network Structurementioning
confidence: 99%
“…57,[95][96][97] These studies have shown specific communication patterns in engineering project management teams in real-world, but have also sparked controversy regarding different communication patterns and performance outcomes. 98 Based on this foundation, the study combines the classic communication networks and summarizes the typical communication networks of engineering project teams. Using the IMO model and classic communication experiments, it analyzes from an innovative perspective the interaction between network structural attributes and network relational attributes.…”
Section: Theoretical Contributionsmentioning
confidence: 99%